"Body self" in the shadow of childhood sexual abuse: The long-term implications of sexual abuse for male and female adult survivors. (February 2018) - Talmon, Anat; Ginzburg, Karni
Abstract: Childhood sexual abuse (CSA) may have long-term negative outcomes for victims' body representations. In this study we examined a model in which the relation between CSA and an individual's discomfort when in close proximity to others is mediated by disrupted body boundaries, and the relation between CSA and body shame is mediated by body self-objectification. Since most of these variables were conceptualized and assessed primarily among women, gender differences regarding the proposed model were examined. Study participants were 843 college/university students (536 women and 307 men). Results from structural equation modeling analyses indicated that in both genders, disrupted body boundaries mediated the relations between CSA and an individual's discomfort when in close proximity to others, as well as between CSA and body shame. Body self-objectification was not associated with history of CSA. Finally, we discuss the role these findings may play in the detrimental long-term effects of CSA on both male and female survivors, and refer to their common underlying mechanism.